Relationship between vertical jump tests and ice-skating performance in junior Polish ice hockey players - Gupta, Subir; Baron, Jakub; Bieniec, Anna; Swinarew, Andrzej; Stanula, Arkadiusz (Biology of Sport, 2023)
The aim of this study was to determine the relationships between vertical jumps (VJ) and various on-ice skating performances of junior ice hockey players (n = 19). The three modes of VJ or off-ice measures were countermovement jump with arm swing (CMJ), squat jump (SJ) and depth drop jump (DDJ). The on-ice skating performance was measured by the skating multistage aerobic test (SMAT), forward and backward acceleration test, top speed test, and repeated sprint ability (RSA) test. The relationships between the variables were quantified using Pearson’s product-moment correlation. DDJ showed a significant positive correlation with forward average skating speed (FASS) (r = 0.62) and strong correlations with backward average skating speed (BASS) (r = 0.81), and maximum skating speed (MSS) (r = 0.71). SJ was found to be strongly correlated with BASS (r = 0.82) and MSS (r = 0.76), whereas the only on-ice performance that significantly correlated with CMJ was BASS (r = 0.68). All three modes of VJ were inversely and non-significantly correlated with performance decrement index and fatigue index, as determined by the RSA test. SMAT was not significantly correlated with either VJ or RSA. Correlations between all three modes of VJ tests were significant. Therefore, this study concludes that: (1) DDJ can be used as a predictor of all the ice skating speed tests, whereas SJ can predict BASS and MSS. CMJ, on the other hand, can predict the performance of only BASS. (2) RSA performance cannot be predicted from CMJ, SJ, or DDJ tests, and (3) neither any of the VJ nor RSA can predict skating endurance of junior ice hockey players.